LATAR BELAKANG PREDESTINASI GANDA JOHN CALVIN: “Historis Kemunculan Predestinasi Abad ke-4 hingga ke Masa Calvin” - Pangeran Manurung (STTII PURWOKERTO, 2021)
The problem in this paper lies in the theological issue of predestination, especially regarding the history of calculating the calvin's version of double predestination. The emergence of the concept of the choice of God over some has created complex theological problems because it was interpreted differently by Calvin's successors. This discussion aims to examine the background to why Calvin taught the extreme predestination formula. Because it focuses on the issue of